Does poor sleep quality affect skin ageing?. (1st January 2015) - Oyetakin‐White, P.; Suggs, A.; Koo, B.; Matsui, M. S.; Yarosh, D.; Cooper, K. D.; Baron, E. D.
Summary: Background: Sleep is important for growth and renewal of multiple physiological systems. The effects of chronic poor sleep quality on human skin function and visible signs of ageing have not been elucidated. Aim: To evaluate the effect of chronic poor sleep quality on measures of skin health and ageing. Self‐perceived satisfaction with appearance was also assessed. Methods: 60 healthy caucasian women, who were categorized as poor quality sleepers [Pittsburg Sleep Quality Index (PSQI) > 5, sleep duration ≤ 5 h] or good quality sleepers (PSQI ≤ 5, sleep duration 7–9 h). A validated clinical tool, SCINEXA TM, was used to assess intrinsic and extrinsic skin ageing. Dark under‐eye circles were evaluated using standardized photos. Measurement of in vivo transepidermal water loss (TEWL) was used to assess recovery of the skin barrier after tape stripping. Subjects were exposed to simulated solar ultraviolet light, and recovery from erythema was monitored. Subjects also completed a questionnaire evaluating self‐perception of attractiveness. Results: Good sleepers had significantly lower intrinsic skin ageing scores by SCINEXA TM . At baseline, poor sleepers had significantly higher levels of TEWL. At 72 h after tape stripping, good sleepers had 30% greater barrier recovery compared with poor sleepers. At 24 h after exposure to ultraviolet light, good sleepers had significantly better recovery from erythema. Good sleepers also reported a significantly better perception of their appearance and physical attractiveness compared with poor sleepers. Conclusions: This study indicates that chronic poor sleep quality is associated with increased signs of intrinsic ageing, diminished skin barrier function and lower satisfaction with appearance.